Pengembangan Platform Pembelajaran Digital Ana Frozen Food Learning untuk Peningkatan Pengetahuan dan Keterampilan - Aliva Genta Gutawa; Fauziah Wulan Sari; Reka Putri; Faradika (CV. ITTC INDONESIA, 2024)
Ana Frozen Food is a company specializing in frozen food, providing a diverse range of high-quality products crafted through meticulous manufacoring processes. With a focus on innovation ad hygiene, Ana Frozen Food ensures thet each product meets food safety standards and offers deightful flavors. Committed to meeting the needs of consumers seeking convenience and quality in frozen food, the company offers a variety of menu options